Effectiveness of innovative techniques on Pupil’s achievement in mathematics among higher secondary students in selected school - Janardhanan, Jayalekshmi; Charles, M. Aron Antony (Edelweiss Applied Science and Technology, 2024)
The incorporation of new teaching strategies into mathematics education has garnered attention in recent times owing to its capacity to augment student engagement and accomplishment. Despite the promising developments, gaps remain in understanding how these methods influence higher secondary students’ performance in mathematics. The purpose of this study was to assess the efficacy of novel approaches in comparison to conventional teaching strategies, examining factors such as teacher competence, student engagement, and socioeconomic influences. The research involved a quasi-experimental design with 200 higher secondary students from selected schools in Kerala. A considerable change in academic accomplishment was found using analysis of variance (ANOVA), with students taught utilizing novel methodologies attaining an average score of 82.5, compared to 79.3 in the traditional group. Additionally, a strong positive correlation (r = 0.68) was found between teacher competence and student performance. The findings showed the critical role of innovative teaching strategies in improving mathematics achievement, highlighting the need for teacher training and curriculum development. The study concludes that embracing these methods can significantly enhance student outcomes, encouraging educators and policymakers to prioritize innovative approaches in mathematics education.